(untitled) (Scientific journal of the Fergana State University, 2024)
This scientific article analyzes the similarities and differences of verbal (oral) aggression in Uzbek and English literature according to their characteristics, semantic and pragmatic connections. The emergence of aggressive behavior, methods of its verbal implementation, the psychological impact of aggression on a person, and the situation after aggression are also analyzed linguistically. In addition, an attempt was made to identify types of verbal aggression such as punishment, examples of behavior related to these types, and examples of increases or decreases in the level of aggression when using them. Verbal aggressive phrases in the English and Uzbek languages were compared and analyzed, and an attempt was made to identify differences and similarities in their use.